PENYEBARAN HAMA Cylas formicarius F. PADA TANAMAN UBI JALAR (Ipomea batatas L.) DI BEBERAPA KETINGGIAN TEMPAT PROPINSI SULAWESI UTARA - Noritha Ahuluheluw; Odi R. Pinontoan; Caroulus S. Rante; Emmy Senewe (Universitas Sam Ratulangi, 2013)
ABSTRACTThis study aims to determine the insect pest population C. formicarius at different altitude. The experiment was conducted in several sweet potato plants centers in the Sinisir Village District of Modoinding South Minahasa Regency, Woloan Village 1 District of Central Tomohon, City of Tomohon, and Sumarayar Village District of Langowan Minahasa regency. The study was conducted from June to December 2012. The things that observed in this study were the number of larvae founded in sweet potato tubers are attacked by pests C. formicarius.The results showed that the average population of the pest C. highest formicarius found sequentially in the Village Sinisir, Sumarayar and Woloan 1, ie 23.0%, 10.0% and 6.8%. Chi-square analysis results as indicating a relationship between altitude and pest population C. formicarius. This is indicated by the value of its asymp sig 0.521 greater than 0.05.Keyword: Cylas formicarius F., Ipomea batatas L. Ubi Jalar, Desa Sinisir, Desa Sumarayar dan Desa Woloan 1